Cutaneous furuncle-like lesions with an unexpected diagnosis: a case report - Silva,Joana Maria Ribeiro (2022)
Abstract Introduction: Myiasis, the infection by a fly larva, usually occurs in tropical and subtropical areas. In non-endemic countries, cutaneous myiasis might become an important condition as the returning traveller might import this infection, expanding the agents’ transmission. Furuncular myiasis mimics common dermatoses, which might lead to misdiagnoses and inadequate treatment. Our purpose is to characterise lesions’ features, helping diagnose, treat and emphasize the relevance of an adequate anamnesis. Case description: A 40-year-old man with an unremarkable medical history, unknown allergies, no medication, and updated vaccination schedule, came upon our primary-health-care unit complaining of three erythematous skin lesions, moderately painful, noticed eight days before. Other symptoms, bites, or similar lesions in the household were denied. While exploring recent travels, the patient reported he had been to São Tomé e Príncipe. On physical examination, three furuncle-like lesions with a central pore were observed. While awaiting travel/tropical medicine advice, an oral antibiotic was prescribed. Hours later, the patient was advised to avoid lesions’ expression and occlude central puncta with petroleum, forcing the organism to emerge and be grasped. The day after, the patient reported larvae extrusion from each lesion. Only skin hyperpigmentation was left after a month. Comment: Furuncular myiasis occurs as a furuncle-like lesion with a central punctum, being the maggot evidenced by visualization of its posterior part. Movement sensations, pruritus, and pain appearing at night are frequently reported. Complete larvae removal and prevention and control of secondary infection are treatment goals. Considering furuncular myiasis among differential diagnoses reduces the unnecessary use of antibiotics and its consequences on resistance. Furthermore, in primary care, there is an optimal opportunity to offer travellers preventive care and health education. Thus, exploring exposures with a detailed clinical history might prevent myiasis-causing flies to become established in non-endemic regions.